Student review of innovations in quantum technologies. Part 5 - Wojciech Buchwald; Maciej Scheffer; Kamil Kośnik; Aleksander Topolewski; Jan Klimas; Jan Mrozowski; Hubert Pogorzelski; Małgorzata Dulikowska; Aleksander Przyborek; Patryk Konwa; Ryszard Romaniuk (International Journal of Electronics and Telecommunications, 2025)
The aim of the paper is to show how graduated engineering students in classical ICT view practically the advent of the QIT. The students do their theses in El.Eng. and ICT and were asked how to implement now or in the future the QIT in their current or future work. Most of them have strictly defined research topics and in some cases the realization stage is advanced. Thus, most of the potential QIT application areas are defined and quite narrow. In such a case, the issue to be considered is the incorporation of QIT components and interfaces into the existing ICT infrastructure, software and hardware alike, and propose a solution as a reasonable functional hybrid system. The QIT components or circuits are not standalone in most cases, they should be somehow incorporated into existing environment, with a measurable added value. Not an easy task indeed. We have to excuse the students if the proposed solutions are not ripe enough. The exercise was proposed as an on-purpose publication workshop, related strictly to the fast and fascinating development of the QIT. The paper is a continuation of publishing exercises with previous groups of students participating in QIT lectures.